Business Processes Re-Engineering: Investigating the Effect of Economic and Environmental Sustainability of Outsourcing Organization in Lagos State - Salau, Odunayo P; Okwaraogoma, Regan O; Aremu, Fisayo J (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study investigated the impact of business process reengineering on outsourcing firms, specifically focusing on Hugo Inc. Process reengineering enables businesses to attain operational efficiency and sustainable practices. Business process reengineering (BPR) is extensively employed to enhance responsiveness, organizational agility, and customer satisfaction by providing superior products and services. Sustainability pertains to the ability of a production method to endure throughout time. BPR seeks to address challenges related to resource management and process implementation. This study aims to elucidate how process reengineering might assist outsourced organizations in achieving more sustainability. A firm must recognize the significance of retaining its clientele and generating profit, as well as the necessity of strategically planning its operations to ensure neither aspect is compromised. The primary components of the study are value generation and process ownership, both of which are associated with business process reengineering. Economic and environmental factors are analyzed in relation to one another and the pertinent issue to assess sustainability. The theoretical foundation of the study was based on the triple bottom line and stakeholder theory. A quantitative survey methodology was employed for this inquiry. The survey encompassed 850 employees, with a sample size of 272 individuals who received questionnaires through purposive and simple random sampling methods. The results indicated a positive correlation between process reengineering and sustainability. The study is different because it seeks to encourage outsourcing firms to reassess their operational strategies to consistently surmount challenges and maintain profitability, and how it can contribute to economic and environmental success.